1994
DOI: 10.1143/jjap.33.l1549
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasoft X-Ray Emission Spectroscopic Analysis for Effects of Vacuum Ultraviolet Rare Gas Excimer Laser Irradiation on Silicon Nitride Films

Abstract: The results of measurements of Si-L2,3 X-ray emission spectra of Si3N4 films deposited on GaAs substrates after irradiation by Kr2 and Ar2 excimer lasers are presented. By using the excitation of X-ray emission spectra with focused electron beam, local precipitation of crystalline silicon is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The precipitation of Si nanoparticles was observed in earlier XES measurements of semiconducting Si 3 N 4 and SiO 2 films induced by excimer laser and electron beam irradiation. 29,30,7 C. Compositional and structural changes during annealing Figure 6 displays the measurements of carbon K␣ XES of PTES films after annealing at 1000°C, and after combined treatments of irradiation and annealing. One observes that the annealing of the unirradiated PTES films modifies the fine structure of the carbon K␣ XES, revealing some spectral features that are typical for spectra of sp 2 hybridized graphite ͑see Fig.…”
Section: B Local Structure Of Irradiated Ptes Filmsmentioning
confidence: 99%
“…The precipitation of Si nanoparticles was observed in earlier XES measurements of semiconducting Si 3 N 4 and SiO 2 films induced by excimer laser and electron beam irradiation. 29,30,7 C. Compositional and structural changes during annealing Figure 6 displays the measurements of carbon K␣ XES of PTES films after annealing at 1000°C, and after combined treatments of irradiation and annealing. One observes that the annealing of the unirradiated PTES films modifies the fine structure of the carbon K␣ XES, revealing some spectral features that are typical for spectra of sp 2 hybridized graphite ͑see Fig.…”
Section: B Local Structure Of Irradiated Ptes Filmsmentioning
confidence: 99%
“…Si L 2,3 x-ray emission spectra (XES) correspond to the 3s → 2p transition, and probe the distribution of the Si 3s partial density of states in the valence band. It was shown in our previous publications [6][7][8] (see also [9]) that for the silicides, c-Si, a-Si, Si 3 N 4 , and SiO 2 , the Si L 2,3 spectra are distinct from each other. On the other hand, measurements of the Si L 2,3 XES at different electron exciting energies can be used for the nondestructive depth-profiling phase analysis, because of a pronounced dependence of the x-ray yield on the electron excitation depth.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, we have constructed depth profiles of elements and phases within interfaces [10]. We used this method for characterization of interfaces in Fe + -implanted Si [10], W/Si multilayers [11], Si 3 N 4 thin films irradiated by an excimer laser [6], and Hf/Si and Ir/Si systems after thermal annealing [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present paper reports on investigations of the local electronic structure of porous and spark-processed silicon utilizing x-ray emission spectroscopy. It has been shown that this technique is very sensitive to the chemical bonding and its modification under different sample treatments in Si-containing materials [17][18][19].…”
Section: Introductionmentioning
confidence: 99%